Community-Based Interventions Philosophy and Action - Murphy, John W.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
For decades, community-centered social services have been promoted as an admirable ideal. Yet the concept of decentralized services delivered where people live has proved to be an elusive ideal as well, with the promise of empowerment often giving way to disinterest and apathy. Community-Based Interventions examines the reasons community programs tend to founder, and proposes a realistic framework for sustained success. The book's theoretical, philosophical, and political foundations begin with the importance of context, as in local knowledge and community self-definition and engagement. Innovative, often startling, approaches to planning, design, and implementation begin with the recognition that communities are not "targets" or "locations" to be "fixed," but social realities whose issues require concrete answers. The variety of examples described in these chapters demonstrate the power of community interventions in providing effective services, reducing inequities, and giving individuals greater control over their health, their environment, and, in the long run, their lives. Included in the coverage: Redefining community: the social dimensions. A new epidemiology to inform community work. The role of research in designing community interventions. The conceptual flow of a community-based project. Building autonomy through leadership from below. Relating social interventions to social justice. Attuned to the current era of health and mental health reform, Community-Based Interventions represents a major step forward in its field, and makes an inspiring text for social workers, clinical social workers, public health administrators, and community activists.
Introduction -- Philosophy and Community-based Interventions -- The Dimensions of a Community -- Community-based Organizations -- A New Epidemiology -- Research and Community -- The Conceptual Flow of a Community-based Project -- Leadership from Below -- Social Interventions and Justice -- Conclusion.
Keywords: Social sciences; Social policy; Social work; Psychology, clinical; Applied psychology; Social Sciences; Social Work; Community and Environmental Psychology; Non-Profit Enterprises/Corporate Social Responsibility; Health Psychology; Social Policy